A method for reactivating spent fcc catalyst by fractional acid leaching and demetallization
Patent Information
- Application Number
- CN202611497495.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-24
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]现有废FCC平衡催化剂处理方法主要包括粒径分离、酸浸、有机酸浸出、铵盐处理、离子交换和焙烧等,粒径分离主要用于筛选污染程度不同的催化剂颗粒,难以脱除保留颗粒中已经沉积的污染金属,液相浸出能够促使部分污染金属迁入液相,但Ni、V和Fe的存在状态及浸出响应不同,采用同一处理条件难以兼顾不同污染金属的脱除
[0012]本发明有益效果为:本发明根据Ni、V和Fe在不同处理环境中的迁移差异,对粒径分级所得主体催化剂依次进行含氢处理、空气条件下的氨水—碳酸铵浸出、中间水洗和草酸酸浸,含氢处理与氨浸体系相配合,提高Ni在前段浸出中的迁移程度,中间水洗以末次洗液pH控制碱性母液的残留程度,减少其对草酸的中和作用,使后段酸浸保持对V和Fe的浸出能力,由此形成前段主要迁移Ni、后段主要迁移V和Fe的连续处理关系,在降低污染金属含量的同时限制Al迁移,并使经离子交换和焙烧所得再活化催化剂保持Y型分子筛结构并提高催化活性。
Smart Images

Figure CN122999295A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalyst regeneration and waste catalyst resource utilization technology, and in particular to a staged acid leaching demetallization and reactivation method for waste FCC catalysts. Background Technology
[0002] During long-term reaction-regeneration cycles, fluidized catalytic cracking catalysts gradually accumulate contaminating metals such as Ni, V, and Fe, accompanied by particle wear, pore blockage, and changes in molecular sieve structure and acidic sites, leading to a decline in catalytic performance. To maintain the operation of the unit, it is necessary to periodically remove a portion of the equilibrium catalyst. This portion of the catalyst usually still retains a certain molecular sieve structure and catalytic activity, and has reuse value.
[0003] Existing methods for treating spent FCC equilibrium catalysts mainly include particle size separation, acid leaching, organic acid leaching, ammonium salt treatment, ion exchange, and calcination. Particle size separation is mainly used to screen catalyst particles with different degrees of contamination, but it is difficult to remove contaminant metals that have been deposited in the particles. Liquid phase leaching can promote the migration of some contaminant metals into the liquid phase, but Ni, V, and Fe have different existence states and leaching responses, making it difficult to achieve the removal of different contaminant metals using the same treatment conditions.
[0004] Furthermore, increasing the leaching intensity may also increase the migration of catalyst components such as Al, thereby affecting the structure and catalytic performance of Y-type molecular sieves. Therefore, the reuse of spent FCC equilibrium catalysts still needs to solve the problem of the difficulty in simultaneously removing different polluting metals and maintaining the structure and performance of the catalyst. Summary of the Invention
[0005] This invention provides a staged acid leaching demetallization and reactivation method for spent FCC catalysts, comprising: The spent FCC equilibrium catalyst was classified by particle size using sieves with pore sizes of 120 μm and 40 μm. The particle size that passed through the 120 μm sieve but did not pass through the 40 μm sieve was taken as the main catalyst. The main catalyst was heated to 390–420°C under a nitrogen atmosphere, and treated with a hydrogen-nitrogen mixture with a hydrogen gas fraction of 8%–12% for 20–25 minutes. Then, the gas was switched to nitrogen and cooled to below 100°C. The main catalyst is added to the first leachate, wherein the mass fraction of NH3 introduced by ammonia water in the first leachate is 3.5%–4.5%, and the effective mass fraction of ammonium carbonate (calculated as (NH4)2CO3) is 2.5%–3.5%. The actual dry mass ratio of the first leachate to the main catalyst before hydrogen treatment is 4.5:1–5.5:1. Under stirring, at 40–45°C, the catalyst is added at a rate of 0.0045–0.0055 L / (g) based on the dry mass. Air is continuously introduced at a flow rate of (min) and ammonia is soaked for 30-60 minutes; After ammonia leaching, solid-liquid separation is performed, and the obtained solid is washed with deionized water until the pH of the final washing solution is 6.5-7.2 at 25±1℃, thus obtaining the first solid catalyst. The first solid catalyst was added to an oxalic acid aqueous solution with an oxalic acid mass fraction of 0.60% to 0.90% (calculated as H2C2O4), wherein the dry mass ratio of the oxalic acid aqueous solution to the first solid catalyst actually entering the acid leaching was 3.5:1 to 4.5:1, and the catalyst was acid-leached at 50 to 60°C for 15 to 30 minutes under stirring. After acid leaching, solid-liquid separation and water washing are performed to obtain a second solid catalyst. The second solid catalyst is then subjected to ammonium nitrate ion exchange, water washing, drying and calcination in sequence to obtain a reactivated FCC catalyst.
[0006] As a preferred embodiment of the staged acid leaching demetallization and reactivation method for the spent FCC catalyst described in this invention, the following steps are taken: before hydrogen treatment, the oxygen volume fraction in the outlet gas is continuously reduced to below 0.5% by nitrogen gas for 1 minute; nitrogen gas is continuously introduced and the temperature is increased to 405°C at 5°C / min; after stabilizing at 405±2°C for 5 minutes, the mixture of hydrogen and nitrogen with a hydrogen gas integral of 10.0% is switched to and treated at 405±2°C for 22.5 minutes; then the mixture is switched to nitrogen gas and cooled to below 80°C. The flow rates of both nitrogen and hydrogen-nitrogen mixtures are 0.010 L / (g) based on the actual dry mass of the main catalyst added before hydrogen treatment. min).
[0007] As a preferred embodiment of the graded acid leaching demetallization and reactivation method for the waste FCC catalyst described in this invention, wherein: the mass fraction of NH3 introduced by ammonia water in the first leachate is 4.00%, the effective mass fraction of ammonium carbonate calculated as (NH4)2CO3 is 3.00%, and the dry mass ratio of the first leachate to the main catalyst actually added before hydrogen treatment is 5.00:1. The ammonia leaching temperature was 42.5±1℃, the leaching time was 45 min, and the air flow rate was 0.0050 L / (g) based on the dry basis mass. The stirring speed is 500 r / min.
[0008] As a preferred embodiment of the graded acid leaching demetallization and reactivation method for the waste FCC catalyst described in this invention, the solid obtained from the solid-liquid separation by ammonia leaching is washed with a slurry. The mass of deionized water added each time is 1.00 times the dry mass of the main catalyst actually added before hydrogen treatment. After washing with a slurry at 25±2℃ and 300r / min for 5min, solid-liquid separation is performed. A total of three slurry washings are performed.
[0009] As a preferred embodiment of the staged acid leaching demetallization and reactivation method for the spent FCC catalyst described in this invention, the oxalic acid aqueous solution contains 0.75% oxalic acid by mass (calculated as H2C2O4), the dry mass ratio of the oxalic acid aqueous solution to the first solid catalyst actually entering the acid leaching is 4.00:1, and the acid leaching is carried out at 55±1℃ and 400r / min for 22.5min. After solid-liquid separation by acid leaching, deionized water was added each time at 1.00 times the dry weight of the first solid catalyst entering the acid leaching process. The mixture was then washed for 5 minutes at 25±2℃ and 300r / min before solid-liquid separation was performed. This washing process was repeated three times.
[0010] As a preferred embodiment of the graded acid leaching demetallization and reactivation method for the spent FCC catalyst described in this invention, the second solid catalyst is subjected to ion exchange using a 6.0% (w / w) ammonium nitrate aqueous solution, wherein the mass of the ammonium nitrate aqueous solution is 5.00 times the dry basis mass of the second solid catalyst actually entering the ion exchange, the ion exchange temperature is 70±1℃, the stirring speed is 400 r / min, and the ion exchange time is 60 min.
[0011] As a preferred embodiment of the graded acid leaching demetallization and reactivation method for the spent FCC catalyst described in this invention, the catalyst after ion exchange is each added with deionized water at 2.00 times the dry weight of the second solid catalyst that actually enters the ion exchange, and is slurried for 10 min at 25±2℃ and 300 r / min, for a total of three slurry washings, and then dried to constant weight at 120±2℃, and then heated to 500℃ at 5℃ / min in air atmosphere and kept at that temperature for 2 h.
[0012] The beneficial effects of this invention are as follows: Based on the migration differences of Ni, V, and Fe in different treatment environments, the main catalyst obtained by particle size fractionation is subjected to hydrogen-containing treatment, ammonia-ammonium carbonate leaching under air conditions, intermediate water washing, and oxalic acid leaching in sequence. The hydrogen-containing treatment and ammonia leaching system are combined to improve the migration degree of Ni in the first stage of leaching. The intermediate water washing controls the residual degree of alkaline mother liquor by controlling the pH of the final washing solution, reducing its neutralization effect on oxalic acid, so that the subsequent acid leaching can maintain the leaching capacity of V and Fe. This forms a continuous treatment relationship in which Ni mainly migrates in the first stage and V and Fe mainly migrate in the second stage. While reducing the content of contaminating metals, it restricts Al migration and makes the reactivated catalyst obtained by ion exchange and calcination maintain the Y-type molecular sieve structure and improve catalytic activity. Attached Figure Description
[0013] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the following description of the embodiments will be briefly introduced. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0014] Figure 1 This is a comparison chart of the migration rates of Ni, V, and Fe in the ammonia leaching stage and the oxalic acid leaching stage in Example 1.
[0015] Figure 2 The graph shows a comparison of the cumulative Al migration rate before ion exchange, final XRD retention rate, and microreactive activity between Example 1 and Comparative Examples 1-4. Detailed Implementation
[0016] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.
[0017] Unless otherwise specified, all catalyst dosages are based on a dry basis. The dosages of the first leachate, the flow rate of the hydrogen-containing mixed gas, the flow rate of the ammonia leaching air, and the dosages of each washing water after ammonia leaching are all calculated based on the actual dry mass of the main catalyst before hydrogen treatment. The dosages of the oxalic acid aqueous solution and the dosages of each washing water after acid leaching are calculated based on the actual dry mass of the first solid catalyst entering acid leaching after deducting the analytical sampling. The dosages of the ammonium nitrate aqueous solution and the dosages of each washing water after ion exchange are calculated based on the actual dry mass of the second solid catalyst entering ion exchange. All gas volumes are calculated at 25°C and 101.3 kPa.
[0018] Among them, the nitrogen purity is not less than 99.999%, the hydrogen-containing mixed gas is a premixed gas of hydrogen and nitrogen, and the composition is based on the gas supply test value, the air is compressed air after oil and water removal, the oxalic acid is analytical grade oxalic acid dihydrate, and the oxalic acid concentration is calculated according to H2C2O4, the ammonium nitrate is analytical grade, and the solution volume is calculated according to the actual purity of the reagent, the nitric acid used for ICP-OES pretreatment is analytical grade, and the ammonia water uses a standardized hydrochloric acid standard titration solution to determine the NH3 mass fraction; Weigh out m1 grams of ammonia water sample, determine the titration endpoint using a methyl red-methylene blue mixed indicator, and perform blank correction. The concentration of the hydrochloric acid standard titration solution is c mol / L. When the sample consumption volume and blank consumption volume are V1 and V0 mL respectively, the NH3 mass fraction is calculated as c × (V1 / V0) mL. Calculate V0)×17.031 / (1000m1)×100%, perform two parallel measurements, and the absolute difference of the results should not exceed 0.10 percentage points.
[0019] The so-called effective mass fraction of ammonium carbonate is the mass fraction calculated as (NH4)2CO3 based on the total acid neutralization capacity of the ammonium carbonate reagent. This value is used for the preparation and measurement of the first leachate and is not equivalent to the chemical purity of ammonium carbonate measured by the component separation method. During the determination, m2 grams of ammonium carbonate sample were weighed and dissolved in boiled and cooled deionized water. Potentiometric titration was performed using hydrochloric acid standard titration solution, with pH 4.50 as the endpoint. Under this endpoint condition, the carbonate and bicarbonate ions in the solution had basically completed the acid neutralization reaction. According to the stoichiometric relationship that 1 mol of (NH4)2CO3 consumes 2 mol of HCl, the amount of hydrochloric acid consumed was converted into the mass of (NH4)2CO3.
[0020] When the concentration of the hydrochloric acid standard titration solution is c mol / L, and the sample consumption volume and blank consumption volume are V2 and V0 mL respectively, the effective mass fraction of ammonium carbonate is calculated according to c × (V2) / V0. The calculation is based on V0)×96.086 / (2000m2)×100%, with two parallel determinations. The absolute difference between the two results is no greater than 0.20 percentage points. The NH3 mass fraction in the first leachate is calculated based only on the NH3 mass introduced by the ammonia water. The ammonium nitrogen introduced by the ammonium carbonate is not included in this value.
[0021] The hydrogen treatment in the baseline scale test used a quartz tube reactor with an inner diameter of 60 mm. The temperature probe was placed in the middle of the bed. The leaching used a jacketed glass reactor with a nominal volume of 1 L and an inner diameter of 100 mm. The reactor was equipped with four baffles with a width of 8 mm and a four-bladed oblique blade with a diameter of 45 mm. The lowest point of the blade was 15 mm from the bottom of the reactor. The bottom gas distribution ring had a diameter of 20 mm and eight pores with a diameter of 0.5 mm were evenly distributed on it. The reactor was connected to a reflux condenser. The temperature of the condensate circulating water was 8 ± 2 °C. The tail gas was absorbed by 200 mL of sulfuric acid solution with a mass fraction of 5%. Except for the scale-up test in Verification Example 7, the other tests used reactors of the same specifications, blade positions, and gas distribution structures. The amount of each assembly material was determined according to the feeding mass and liquid-solid ratio specified in the corresponding embodiment, verification example, or comparative example. Verification Example 7 used the scale-up device explicitly described in that example.
[0022] Before hydrogen treatment, the gas is purged with nitrogen. The outlet gas enters an oxygen analyzer with a range of 0-5% through the sampling port between the reactor outlet and the tail gas absorption bottle. The oxygen analyzer is calibrated with high-purity nitrogen and standard gas with an oxygen volume fraction of 1.00% before each batch of tests. After the outlet oxygen volume fraction is continuously below 0.5% for 1 minute, nitrogen is kept flowing in and the temperature is increased to the set temperature at 5℃ / min. The temperature is stabilized for 5 minutes, and then the hydrogen-nitrogen mixture with the set composition is switched on. The hydrogen treatment time is calculated when the hydrogen-nitrogen mixture reaches the set flow rate.
[0023] Immediately after the hydrogen treatment is completed, the hydrogen-nitrogen mixture is shut off, and nitrogen is switched at the same total flow rate and cooled under nitrogen protection.
[0024] Particle size classification was performed using a metal wire woven mesh test sieve and a mechanical vibrating sieve conforming to GB / T 6003.1. Each feeding onto the sieve surface did not exceed 250g, the vibration frequency was 220 times / min, and the amplitude was 3mm. First, the particles on the sieve were removed using a 120μm sieve, and then the particles on the sieve were collected using a 40μm sieve. After the specified sieving time was reached, the sieving continued for 1min. The sieving ended when the mass of the newly added material under the sieve did not exceed 0.10% of the dry basis mass of the feed for that grade. If this condition was not met, the sieving time was extended by 1min each time until the endpoint was met. When the sieve holes were blocked, the back of the sieve was cleaned with a soft brush.
[0025] Solid-liquid separation after ammonia leaching, acid leaching, and each washing cycle was performed using glass fiber membranes with a nominal pore size of 1 μm, and the filtration vacuum degree was [missing information]. 0.06~ After ammonia leaching or acid leaching at 0.08 MPa, the reaction slurry is quantitatively transferred. The reactor, agitator, and gas distribution pipe are rinsed three times with 20.00 g of deionized water. The resulting rinsing liquid is combined with the corresponding reaction slurry and then filtered. After filtration, the filter bottle and connecting pipe are quantitatively rinsed with 10.00 g of deionized water. The resulting rinsing liquid is combined with the aforementioned filtrate. The combined liquid phase is recorded as the main filtrate of the corresponding leaching stage. The 30.00g of equipment rinsing water mentioned above is not included in the amount of filter cake slurry washing water used.
[0026] Each solid slurry washing uses only the deionized water specified in the corresponding example or verification example, without adding additional equipment rinsing water, and the slurry from each washing is collected separately.
[0027] Before metal determination, the main filtrate and each solid washing solution in both stages were passed through a hydrophilic filter membrane with a nominal pore size of 0.45 μm. The term "solid-free liquid phase" refers to the liquid phase obtained after passing through this 0.45 μm filter membrane.
[0028] The process liquid samples used for pH measurement and metal analysis were all taken from fixed sampling ports at the same height of the reactor. The initial sample for ammonia leaching was taken when nitrogen gas was stopped being introduced into the upper part of the reactor but before air was introduced from the bottom. The final sample for ammonia leaching was taken when the specified ammonia leaching time was reached but before air introduction was stopped. The initial sample for acid leaching was taken when the slurry reached the specified temperature but before acid leaching time was calculated. The final sample for acid leaching was taken when the specified acid leaching time was reached but before heating was stopped.
[0029] Each sampling uses a clean liquid phase sampler, which consists of a porous support head immersed in the reaction slurry, a hydrophilic filter membrane with a nominal pore size of 0.45μm covering the outside of the porous support head, a sealed sampling tube, and a syringe connected to the sealed sampling tube. During sampling, negative pressure is generated by a syringe, and the liquid phase passes through the hydrophilic filter membrane and enters the sealed sampling tube. The catalyst solid is retained in the reactor by the hydrophilic filter membrane. The obtained liquid phase is transferred to a pre-weighed capped sample bottle, and 3.00g of liquid sample is obtained based on the mass difference before and after sampling in the sample bottle.
[0030] After obtaining the liquid sample, immediately seal the sample bottle and place it in a constant temperature water bath at 25±1℃. After the liquid sample temperature reaches 25±1℃, use a low-volume composite pH electrode to measure the pH. After the pH measurement is completed, the density of the process liquid sample at 25°C is measured using a calibrated 1.00 mL micro-density bottle before acidification. After the density measurement solution is quantitatively transferred back to the original sample bottle, the entire process liquid sample is acidified and used for ICP-OES determination. Its entire original mass is included in the corresponding leaching stage and is not returned to the reactor.
[0031] The pH meter is calibrated in segments according to the range of the sample to be tested: the acid leaching process solution uses standard buffer solutions with pH 1.68, 4.00 and 6.86 at 25℃, the final washing solution uses standard buffer solutions with pH 4.00, 6.86 and 9.18, and the ammonia leaching process solution uses standard buffer solutions with pH 6.86, 9.18 and 12.45. After calibration, the electrode slope is 95% to 105% of the theoretical slope, and the corresponding standard buffer backtest deviation does not exceed 0.03.
[0032] After each solid-liquid separation of the slurry is completed, the washing solution is thoroughly mixed, 20 mL is placed in a covered beaker, and the pH is measured twice after standing at 25±1℃ for 5 min. The average value is taken when the difference between the two results does not exceed 0.05, and this average value is used as the pH of the washing solution for this time. The main filtrate from ammonia leaching, the main filtrate from acid leaching, and each washing solution were weighed separately, and their densities were determined at 25°C using a calibrated density bottle. The mass and density of the process liquid samples were determined according to the aforementioned method.
[0033] Nitric acid was added to the liquid sample to make the mass fraction of nitric acid in the test solution approximately 2%, and the solution was quantitatively diluted and then analyzed by ICP-OES. The analytical lines for Ni, V, Fe, and Al were 231.604 nm, 292.402 nm, 238.204 nm, and 396.152 nm, respectively. The working curve concentrations for Ni, V, and Fe were 0, 0.10, 0.50, 1.00, 5.00, and 10.00 mg / L, and the working curve concentrations for Al were 0, 0.50, 2.00, 10.00, 25.00, and 50.00 mg / L. Unweighted linear regression was used, and the correlation coefficient of the calibration curve was not less than 0.9995. The relative deviation of the back-calculated concentration at each non-zero calibration point did not exceed 5%. Samples exceeding the curve range were further quantitatively diluted.
[0034] Each test solution was injected three times consecutively. The relative standard deviation was calculated by dividing the sample standard deviation by the average value and multiplying by 100%. The result should not exceed 2.0%. Each batch was checked with an intermediate concentration calibration solution. The relative deviation was calculated by dividing the absolute value of the difference between the measured value and the standard value by the standard value and multiplying by 100%. The result should not exceed 5%. For each independent experiment, one sample was selected from both the ammonia leaching main filtrate and the acid leaching main filtrate for spiked recovery testing. For each selected sample, unspiked, 50% spiked, and 100% spiked samples were prepared. Here, 50% and 100% refer to the fact that the mass of the corresponding metal standard added is equivalent to 50% and 100% of the measured mass of the corresponding metal in the unspiked sample, respectively. Before final volume adjustment, the corresponding metal standard solution was added to each spiked sample. The spike recovery rate was calculated by dividing the difference between the measured mass of the corresponding metal in the spiked sample and the measured mass of the corresponding metal in the unspiked sample by the actual mass of the corresponding metal added and multiplying by 100%. The spike recoveries of Ni, V, Fe and Al at both spiking levels should be 95% to 105%.
[0035] The mass of the corresponding metal in the j-th liquid phase is calculated using the following formula: m j =C j ×D j ×M j / (1000ρ j ); In the formula, m j The mass of the metal in the j-th liquid fraction is expressed in mg, C. j The metal concentration measured by ICP-OES is expressed in mg / L. j M is the total dilution factor for this liquid phase. j The mass of the liquid phase is expressed in grams (g), ρ j This is the density of the liquid phase at 25°C, expressed in g / mL.
[0036] The ammonia leaching stage consists entirely of solid-free liquid phases, including the main ammonia leaching filtrate, the water washing liquids of the first solid catalyst, and the liquid samples from the ammonia leaching process. The migration rate of the ammonia leaching stage is the percentage of the sum of the corresponding metal masses in the above liquid phases relative to the corresponding metal masses in the main catalyst actually added before hydrogen treatment.
[0037] The acid leaching stage consists entirely of solid-free liquid phases, including the main acid leaching filtrate, the washing solutions of the second solid catalyst, and the liquid samples from the acid leaching process. The migration rate during the acid leaching stage is the percentage of the sum of the corresponding metal masses in the above liquid phases to the corresponding metal mass in the first solid catalyst that actually enters the acid leaching process.
[0038] The total migration rates of Ni, V, and Fe in the two stages are the percentage of the sum of the corresponding metal masses in the solid-free liquid phase of both leaching stages to the corresponding metal masses in the main catalyst actually added before hydrogen treatment. The cumulative migration rate of Al is calculated using the same method.
[0039] The mass balance recovery rate of the ammonia leaching stage is the percentage of the corresponding metal mass in the total solid-free liquid phase of the ammonia leaching stage and the corresponding metal mass before the first solid sampling, relative to the corresponding metal mass in the main catalyst actually added before hydrogen treatment. The mass balance recovery rate of the acid leaching stage is the percentage of the corresponding metal mass in the total solid-free liquid phase of the acid leaching stage and the corresponding metal mass before the second solid sampling, relative to the corresponding metal mass in the first solid catalyst actually entering the acid leaching stage.
[0040] When the mass balance recovery rate is 95% to 105%, the corresponding migration rate data are used for comparison. If it exceeds this range, first check the liquid transfer, sampling amount, dilution factor, liquid density, solid water content and solid metal mass fraction. If the mass balance recovery rate still cannot reach 95% to 105% after checking, repeat the test. The original test results are not used for migration rate comparison.
[0041] Unless otherwise stated, the term "drying to constant weight" in this invention refers to the process of drying a sample at a specified temperature for the first time, then cooling it in a desiccator for 30 minutes and weighing it, followed by drying for another 30 minutes at the same temperature, cooling it, and weighing it again, until the difference between the weighing values of two consecutive drying and cooling cycles does not exceed 0.2% of the previous weighing value, and the final weighing value is taken as the mass after drying.
[0042] The moisture content of both the catalyst raw material and the wet filter cake was determined by gravimetric method. When determining the moisture content of the catalyst raw material, 1.500g of the raw material sample obtained by the quartering method was weighed after thorough mixing. When determining the moisture content of the wet filter cake, the wet filter cake was thoroughly mixed, and equal amounts of samples were taken from the top, middle and bottom parts and weighed together. The samples were dried at 105±2℃ for 2h. After that, the drying, cooling and weighing were continued according to the aforementioned constant weight criterion until constant weight was achieved.
[0043] The total carbon mass fraction in the waste FCC equilibrium catalyst raw material and the main catalyst obtained by sieving was determined by high temperature combustion-infrared absorption method. The raw material test sample was thoroughly mixed, dried to constant weight at 105±2℃, ground and passed through a 75μm sieve. 0.5000g of the sample was weighed and placed in a ceramic crucible. It was burned in oxygen with a purity of not less than 99.995% at 1350±20℃ to convert the carbon in the sample into CO2. The carbon content was then quantified using a non-dispersive infrared detector. The instrument is calibrated using certified carbon reference materials that are appropriate for the carbon content of the sample. Blank tests are performed simultaneously on each batch of samples. Each sample is measured independently three times. The average value is taken when the relative standard deviation of the three results does not exceed 5.0%, and the total carbon content is expressed as a dry basis mass fraction. If it exceeds 5.0%, the sample is remixed, resampled, and measured.
[0044] The moisture content is calculated as the percentage of the difference in mass of the sample before and after drying to the mass of the sample before drying. The mass of the wet filter cake base is calculated by multiplying the total mass of the wet filter cake by one and subtracting the moisture content.
[0045] Ni, V, Fe and Al in the solid sample were determined by melt digestion-ICP-OES method. The solid sample dried to constant weight at 105±2℃ was ground and passed through a 75μm sieve. 0.1000g of sample was weighed, and 0.6000g of lithium tetraborate and 0.3000g of lithium metaborate were added. After mixing, the sample was melted at 1000℃ for 15min. The resulting molten material was dissolved in 50 mL of 5% nitric acid at 80 °C, cooled, and then brought to a final volume of 100.00 mL. Ni, V, Fe, and Al were then determined according to the analytical lines, calibration curves, and quality control requirements used in liquid chromatography-ICP-OES. Each solid sample was independently melt-tested twice. If the relative deviation between the two test results did not exceed 3.0%, the average value was taken. If it exceeded 3.0%, the sample was prepared again for testing. The metal mass in the stage solid was calculated by multiplying the dry basis mass of the solid in that stage by the corresponding metal mass fraction. The dry basis mass and metal mass corresponding to the first solid analysis sample were deducted from the acid leaching feed, and the dry basis mass corresponding to the second solid analysis sample were deducted from the ion exchange feed.
[0046] Take 0.8000g of dried catalyst sample that has passed through a 75μm sieve, mix it with 0.2000g of α-Al2O3 internal standard, grind it in an agate mortar for 5min, load the sample using the same back-mounted sample holder, scrape the surface flat without compacting it, and detect it using Cu Kα radiation with a tube voltage of 40kV, a tube current of 40mA, a 2θ scan range of 5°~40°, a step size of 0.02°, and a scan speed of 2° / min.
[0047] The pre-scan spectrum of the host catalyst without internal standard showed no indistinguishable α-Al2O3 crystal phase peaks in the 25.4°–25.8° range. For the Y-type molecular sieve characteristic peaks above the baseline, the lines connecting the two endpoints of each integration interval were used as the baseline. The α-Al2O3 internal standard peaks were integrated using the 25.4°–25.8° range and the same method. The sum of the peak areas of the six Y-type molecular sieves is divided by the internal standard peak area to obtain the normalized peak area. Each sample is prepared independently three times, and the average value is taken. The relative standard deviation of the three normalized peak areas does not exceed 2.0%. The peak area retention rate is the ratio of the normalized peak area of the treated sample to the normalized peak area of the main catalyst before treatment.
[0048] Before evaluation, both the main catalyst and the reactivated catalyst were treated in air at 500℃ for 2 hours, cooled, and then stored in a sealed container. The same batch of vacuum gas oil was used for the evaluation, with a density of 0.892 g / cm³ at 20℃, and distillation temperatures of 356℃, 421℃, and 503℃ for 10%, 50%, and 90% concentrations, respectively. The residual carbon mass fraction was 0.28%, and the sulfur mass fraction was 0.67%. 5.00 g of catalyst was loaded into a fixed-bed microreactor tube with an inner diameter of 15 mm and a bed height of about 35 mm. The temperature was raised to 460 °C under nitrogen protection at a rate of 60 mL / min. 1.33 g of feed oil was continuously added over 75 s. After the feed was completed, nitrogen was purged at a rate of 60 mL / min for 15 min. The liquid product was collected and weighed in a 0 °C cold trap, and the gaseous product was collected quantitatively.
[0049] Gaseous products were determined by dual-channel gas chromatography: permanent gases were determined using a molecular sieve column and a thermal conductivity detector, while C1–C4 hydrocarbons were determined using a porous open-tube column and a flame ionization detector. Five-point calibration curves were prepared for each component using certified mixed gases with a correlation coefficient of not less than 0.999. The mass of the gaseous products was calculated based on the collection volume, composition, and molar mass of each component at 25°C and 101.3 kPa. Carrier nitrogen was not included in the product mass.
[0050] Liquid products were measured using a non-polar high-temperature simulated distillation column with a length of 5 m, an inner diameter of 0.53 mm, and a film thickness of 0.15 μm and a hydrogen flame ionization detector. The injection port and detector temperatures were 350 °C and 370 °C, respectively. The helium flow rate was 8.0 mL / min, the injection volume was 1.0 μL, and the split ratio was 20:1. With C5~C 44 To establish the relationship between retention time and boiling point for n-alkanes, the column temperature was increased from 40℃ for 1 min and then increased to 360℃ at a rate of 10℃ / min and held for 5 min. Based on this, the mass of the portion with a boiling point above 221℃ was calculated.
[0051] After the reaction, all catalysts were burned in oxygen at 600℃ and 100mL / min. The generated CO2 was quantified by an infrared detector. Combustion was stopped when the signal recovered to the blank baseline and was maintained for 5 minutes. The carbon standard material was used for calibration and the blank value of unreacted catalyst was subtracted. Microreaction activity is the percentage of the difference between the mass of the feedstock oil and the mass of the liquid product with a boiling point higher than 221℃, relative to the mass of the feedstock oil. The CO2 obtained from the combustion of the catalyst after the reaction is converted into the mass of deposited carbon based on the mass of carbon elements. The total mass recovery rate is calculated by dividing the sum of the masses of gaseous products, liquid products, and deposited carbon by the mass of the feedstock oil and multiplying by 100%. The result should be 97% to 103%. Each catalyst is evaluated independently three times, and the range of the results should not exceed 1.0 percentage point.
[0052] The amount of mother liquor entrained in the wet filter cake was traced using ammonium bromide parallel tracers. Bromine ions were separated using an anion exchange column. 20 mmol / L potassium hydroxide was used as the eluent at a flow rate of 1.0 mL / min. The detection was performed using suppressed conductivity. The working standard solution concentrations were 0, 1, 5, 10, 25 and 50 mg / L. Quantitative dilution was performed when the sample exceeded the calibration range. The wet filter cake was extracted twice with 50.00g of deionized water, stirring for 10min each time and then filtered. The extracts were weighed and their density and bromide ion concentration were measured. The tracer recovery rate was determined using a known addition experiment. A tracer-free wet filter cake with the same dry basis mass as the experiment was taken, and 10.00 mL of ammonia leaching mother liquor with a known bromide ion mass concentration was added. After standing for 2 min, the extract was extracted using the same method. The sum of the bromide ion mass in each extract was divided by the added bromide ion mass and multiplied by 100% to obtain the recovery rate. The experiment was repeated three times. Let the sum of the bromide ion masses in the two extracts be mBr (mg), the recovery rate be R (expressed as a decimal), the bromide ion concentration in the mother liquor before filtration be CBr (mg / L), and the density of the mother liquor at 25℃ be ρm (g / mL). Then, the entrained mother liquor mass is calculated as mm_mother_liquid = 1000mBrρm / (RCBr) (g).
[0053] Example 1; The same batch of waste FCC equilibrium catalyst, sufficient to complete Example 1, the verification example, and the comparative example, was obtained from the regenerator equilibrium catalyst discharge outlet of the same FCC unit. It was placed in a polyethylene container and rolled and mixed for 10 minutes. Then, it was divided into quarters and 200g was taken as raw material test sample. The remaining raw materials were sealed and stored. Particle size classification was carried out in batches according to the feeding scale of each example, verification example, and comparative example. The raw material test sample was thoroughly mixed, and its moisture content and total carbon mass fraction were determined according to the general method. 1.5000g of raw material test sample was weighed and dried to constant weight, and the mass was 1.4871g. Based on this, the moisture content of the raw material was calculated to be 0.86%. The three independent determination results of the total carbon mass fraction of the raw material were 0.482%, 0.476% and 0.485%, respectively, with an average value of 0.481% and a relative standard deviation of 0.95%.
[0054] 1008.7g of waste FCC equilibrium catalyst was weighed according to the moisture content of the raw material, corresponding to a dry basis mass of 1000.0g. Particle size was classified using 120μm and 40μm test sieves according to the aforementioned general method. The specified sieving time for both stages was 10min. The mass of newly added undersize material after 1min of sieving was 0.42g and 0.36g, respectively, both of which met the sieving endpoint criteria. After sieving, based on dry weight, 103.5 g of fine powder smaller than 40 μm, 843.8 g of catalyst of 40–120 μm, and 49.6 g of particles larger than 120 μm were obtained, with a sieve dry weight recovery rate of 99.69%.
[0055] The 40–120 μm catalyst was sealed and mixed for 5 min to serve as the main catalyst. 3.0 g samples were taken from the upper, upper-middle, middle, lower-middle, and lower layers of the mixture and combined. After thorough mixing, the combined samples were used to determine the metal content and total carbon content. The mass fractions of Ni, V, Fe, and Al were found to be 0.910%, 0.360%, 0.710%, and 22.80%, respectively. The three independent determinations of the total carbon mass fraction of the main catalyst were 0.461%, 0.466% and 0.463%, respectively, with an average of 0.463% and a relative standard deviation of 0.54%.
[0056] 100.00g of the main catalyst was weighed and loaded into a quartz tube reactor with a bed height of 45mm. The bed was purged with nitrogen at 1.00L / min for 20min according to the aforementioned general method. After the outlet oxygen volume fraction reached the specified criterion, the temperature was increased to 405℃ at 5℃ / min and stabilized for 5min. The flow rate was then switched to a hydrogen-nitrogen mixture with a hydrogen gas fraction of 10.0% and a flow rate of 1.00L / min. The mixture was treated at 405±2℃ for 22.5min. Then, the flow rate was switched to nitrogen at 1.00L / min for cooling. After the bed temperature dropped to 80℃, the mixture was transferred to a sealed transfer container that had been purged with nitrogen and cooled further to 25±2℃.
[0057] The mass fraction of NH3 in the ammonia solution was measured to be 24.86%, and the effective mass fraction of ammonium carbonate was 98.7%. Weigh 80.45g of ammonia water, 15.20g of ammonium carbonate and 404.35g of deionized water to prepare 500.00g of the first leachate, in which the mass fraction of NH3 introduced by the ammonia water is 4.00% and the effective mass fraction of ammonium carbonate calculated as (NH4)2CO3 is 3.00%.
[0058] Add 480.00 g of the first leachate to the jacketed reactor, purge the upper space of the reactor with nitrogen at 0.20 L / min for 5 min, and then add the cooled main catalyst within 2 min under nitrogen protection. The remaining 20.00g of the first leachate was used to rinse the quartz tube reactor and the transfer container three times. All the rinse solution was transferred into the jacketed reactor without adding deionized water. Based on the mass difference between the quartz tubular reactor and the transfer container before and after feeding, the actual dry mass of the main catalyst entering the ammonia leaching reactor is 100.00g, and the total amount of the first leachate is 500.00g.
[0059] Close the feed port and stir at 500 r / min for 3 min. After the slurry temperature reaches 42.5±1℃, stop introducing nitrogen into the upper part of the reactor and continuously introduce air from the bottom at 0.50 L / min and start timing. The air flow rate is equivalent to 0.0050 L / (g dry base catalyst·min). Ammonia leaching is carried out at 42.5±1℃ and 500 r / min for 45 min.
[0060] Initial and final ammonia leaching samples were obtained according to general sampling and determination methods, and their pH values at 25±1℃ were measured to be 10.46 and 10.21, respectively.
[0061] After ammonia leaching, stop aeration and heating, continue stirring for 1 minute, quantitatively transfer and filter according to general methods. Add 100.0 g of deionized water to the first solid catalyst each time, wash for 5 minutes at 25±2℃ and 300 r / min, and then filter. Wash three times in total. The pH of the three washing solutions at 25±1℃ are 9.08, 7.47 and 7.02, respectively. Each liquid phase was measured and tested separately according to the general method. The mass of the first wet filter cake was 128.60g. After mixing, 1.500g was taken and the water content was measured to be 24.73%. Based on this, the dry basis mass of the first solid catalyst before sampling was calculated to be 96.797g. The dry basis mass corresponding to the wet sample was 1.129g. After deducting the sample and its contained metals, the actual dry basis mass of the first solid catalyst entering acid leaching was 95.668g.
[0062] The measured purity of oxalic acid dihydrate was 99.5%. Based on a dry basis mass ratio of 4.00:1 between the oxalic acid aqueous solution and the first solid catalyst actually entering the acid leaching process, 382.672 g of oxalic acid aqueous solution was prepared, including 4.039 g of oxalic acid dihydrate and 378.633 g of deionized water. The mass fraction of oxalic acid in the resulting solution, calculated as H2C2O4, was 0.75%.
[0063] The first solid catalyst and oxalic acid aqueous solution were added to the jacket reactor and acid leached at 55±1℃ and 400r / min for 22.5min. The initial and final acid leaching liquid samples were obtained according to the aforementioned general method, and the pH of the two samples were 1.86 and 2.03, respectively. Then stop heating, introduce 20°C circulating water into the jacket, and reduce the slurry temperature to below 45°C within 2 minutes. Then transfer and filter quantitatively according to the general method. Each time, the second solid catalyst is added to deionized water at 1.00 times the dry weight of the first solid catalyst that actually enters the acid leaching process. After washing for 5 minutes at 25±2℃ and 300r / min, solid-liquid separation is performed. The washing is repeated three times. The main filtrate from the acid leaching process, the washing solutions from each process, and the liquid samples from the acid leaching process are all measured and tested according to the aforementioned general method.
[0064] The second wet filter cake weighed 124.5g. After mixing, 1.500g was taken and the moisture content was measured to be 24.02%. The dry basis weight of the second solid catalyst before sampling was 94.595g. After deducting the 1.140g dry basis weight corresponding to the wet sample, the dry basis weight of the second solid catalyst entering the ion exchange was 93.455g.
[0065] The measured purity of ammonium nitrate was 99.8%. 467.275 g of a 6.0% ammonium nitrate aqueous solution was prepared according to 5.00 times the dry weight of the second solid catalyst that actually entered the ion exchange, including 28.093 g of ammonium nitrate and 439.182 g of deionized water. Ion exchange was performed at 70±1℃ and 400r / min for 60min, followed by filtration after cooling to below 40℃. After ion exchange, deionized water was added to the filter cake at a rate of 2.00 times the dry weight of the second solid catalyst that actually entered the ion exchange each time, i.e., 186.91g of deionized water was added each time. After washing for 10 minutes at 25±2℃ and 300r / min, solid-liquid separation was performed. The washing was repeated three times in total.
[0066] The obtained catalyst was first dried at 120±2℃ for 4 hours, and then dried, cooled and weighed according to the aforementioned constant weight criterion until constant weight was achieved. The dried catalyst was spread evenly in an alumina crucible with a layer thickness of 10-12 mm. The temperature was increased to 500°C at 5°C / min in air and held for 2 hours. After cooling to below 100°C in the furnace, the catalyst was transferred to a dryer and cooled to room temperature to obtain 91.9 g of reactivated FCC catalyst. The final product is sampled from the upper, middle and lower layers in equal quantities and combined to determine the metal mass fraction, the retention rate of the integral area of the characteristic peak of the Y-type molecular sieve, and the micro-reaction activity.
[0067] Table 1: Metal mass balance and phased migration results of Example 1
[0068] The Ni / V and Ni / Fe migration ratios in the ammonia leaching stage were 6.54 and 7.32, respectively, while the V / Ni and Fe / Ni migration ratios in the oxalic acid leaching stage were 6.69 and 5.31, respectively. This indicates that Ni mainly migrates during the ammonia leaching stage, while V and Fe mainly migrate during the oxalic acid leaching stage. The comparison of migration rates at each stage is as follows: Figure 1 As shown.
[0069] Table 2: Detection results of the main catalyst and the reactivated FCC catalyst
[0070] As shown in Table 2, the reactivation treatment reduced the contents of Ni, V and Fe, and the resulting catalyst maintained the Y-type molecular sieve structure and improved microreactor activity.
[0071] Table 3: Independent Reproducibility Results of Process in Example 1
[0072] R1 to R3 were three independent treatments performed after sampling from the homogenized main catalyst. They were not repeated injections of the same test solution. Each test met the quality control requirements for stage migration rate, Al cumulative migration rate, XRD retention rate, and microreactor activity evaluation.
[0073] The main catalysts of verification examples 1 to 4 and comparative examples 1 to 4 were prepared separately and uniformly homogenized using the same sampling batch as in example 1 and the particle size classification method of example 1. Except for Verification Example 4, which was sampled at the first solid catalyst layer obtained after ammonia leaching and three water washings as specified in that example, all other groups were fed with 100.00g of dry basis before hydrogen treatment; The raw material source, particle size, and feeding scale for verification examples 5-7 shall be performed in accordance with the specific records of each example; Except for the changes listed in the table and other examples, the reactor specifications, impeller position, gas distribution structure, feeding sequence, liquid phase collection, sampling, detection and calculation methods are the same as in Example 1; When using the midpoint conditions, the hydrogen treatment conditions are 405℃, H2 volume fraction of 10.0% and 22.5 min, the ammonia leaching conditions are 42.5℃ and 45 min, and the acid leaching conditions are 55℃ and 22.5 min.
[0074] Verification Example 1; The hydrogen-containing treatment temperature, hydrogen gas fraction, and treatment time were changed respectively. Subsequent ammonia leaching and acid leaching were carried out under the midpoint conditions of Example 1. Each group was treated until the second solid water washing was completed.
[0075] Table 4: Hydrogen-containing treatment conditions and migration results during the ammonia leaching stage
[0076] Table 5: Migration results of the acid leaching stage under hydrogen-containing treatment conditions
[0077] Tables 4 and 5 show that hydrogen-containing treatment conditions can take into account the migration of Ni in the ammonia leaching stage, the two-stage metal migration relationship, and the retention of Al. When the temperature is below the range, the degree of Ni migration decreases, while when the temperature is above the range, the degree of migration of V and Fe in the ammonia leaching stage and Ni and Al in the acid leaching stage increases.
[0078] Verification Example 2; Each group completed the hydrogen-containing treatment according to the above midpoint conditions, and changed the mass fraction of NH3 introduced by ammonia water, the effective mass fraction of ammonium carbonate, the liquid-solid ratio, the ammonia leaching temperature, the ammonia leaching time, and the air flow rate respectively. The subsequent acid leaching was carried out according to the conditions of Example 1.
[0079] Table 6: First Leachate, Ammonia Leaching Conditions, and Migration Results During the Ammonia Leaching Stage
[0080] Note: The nitrogen flow rate for the nitrogen-air replacement group is calculated based on 25℃ and 101.3kPa and is the same as the corresponding air flow rate.
[0081] Table 7: Migration results of the acid leaching stage under the first leachate and ammonia leaching conditions
[0082] Tables 6 and 7 show that the composition of the first leachate and the aeration conditions can maintain the main migration of Ni in the ammonia leaching stage and ensure that the subsequent oxalic acid leaching maintains the migration effect on V and Fe. Removing ammonium carbonate or replacing air with nitrogen will reduce the degree of Ni migration in the ammonia leaching stage and its migration relationship with V and Fe.
[0083] Verification Example 3; Five independent experiments were set up. After hydrogen treatment, ammonia immersion and filtration were completed in each group according to Example 1, the group was washed with deionized water at 25±2℃ and 300r / min for 5min and then solid-liquid separation was performed. The pH of the final washing solution was controlled only by the cumulative washing water volume.
[0084] The cumulative washing water volume in Table 8 is calculated based on the above dry basis mass standard. For groups with a cumulative washing water volume of 2.00 g / g, 3.00 g / g, and 4.00 g / g, deionized water is added each time at 1.00 times the dry basis mass. For groups with a cumulative washing water volume of 2.50 g / g and 3.50 g / g, after completing the corresponding integer number of washing cycles, deionized water is added at 0.50 times the dry basis mass for one more washing cycle. After completing the specified washing cycle, acid leaching is performed.
[0085] Table 8: Migration Results During Intermediate Washing and Acid Immersion Stages
[0086] Table 8 shows that when the pH of the final washing solution is within the above range, the subsequent oxalic acid leaching can maintain the migration effect on V and Fe. When the pH of the final washing solution is higher than the above range, the migration degree of V and Fe decreases while the migration degree of Ni increases. Therefore, the pH range is taken as the water washing endpoint between the two leaching stages.
[0087] Verification Example 4; Nine batches of parallel pretreatment were set up using the above-mentioned uniformly homogenized main catalyst. Each batch was fed at 100.00g dry basis and under the same conditions as in Example 1, hydrogen treatment, ammonia leaching and three water washing were completed. The first solid catalysts obtained from the nine batches were combined and mixed in a closed rolling system for 10 minutes. After determining the moisture content according to the general method, the moisture content and metal analysis samples were deducted, and the samples were divided into nine groups with an equal amount of 95.00g dry basis. The only changes in each group were the oxalic acid mass fraction (calculated as H2C2O4), the oxalic acid aqueous solution to the dry basis mass ratio of the first solid catalyst, the acid leaching temperature, and the acid leaching time. All other acid leaching, solid-liquid separation, liquid phase collection, sampling, detection, and calculation conditions were the same as in Example 1.
[0088] Table 9: Oxalic acid treatment conditions and migration results during acid leaching.
[0089] Table 9 shows that the oxalic acid treatment conditions can balance the migration of V and Fe, the restriction of Ni migration, and the retention of Al. When the oxalic acid mass fraction is below the above range, the migration of V and Fe decreases, and when it is above the above range, the migration of Ni and Al increases.
[0090] Verification Example 5; Batch A, B, and C were taken from different operating cycles of the same FCC unit, while batches D and E were taken from two other FCC units, respectively. All batches of raw materials were particle size-graded according to Example 1, and the resulting main catalyst was fed at a dry basis of 100.00 g. All processing and testing were completed under midpoint conditions. Except for the source of raw materials and initial composition, the processing conditions, sampling, testing, and calculation methods were identical for each batch.
[0091] Table 10-1: Composition and Absolute Migration Rate of Different Raw Material Batches
[0092] Table 10-2: Selection Relationship and Reactivation Results of Different Raw Material Batches
[0093] Tables 10-1 and 10-2 show that the host catalysts from different sources and with different initial compositions all exhibit a consistent staged metal migration trend after being treated by this method, and can limit Al migration, maintain the Y-type molecular sieve structure, and improve microreactor activity.
[0094] Verification Example 6; Particle sizes smaller than 40 μm, 40–120 μm, and larger than 120 μm were collected from the same homogenized raw material, and one group of unclassified raw material was retained. The initial mass fractions of Ni, V, Fe, and Al, as well as the microreactor activity before treatment, were determined for each group.
[0095] Each group was fed with 100.00g of dry material and treated under the midpoint conditions of Example 1. For particle sizes larger than 120μm, sufficient samples were obtained by increasing the amount of raw material sieve.
[0096] Table 11: Initial composition and processing results of different particle sizes
[0097] Al particles smaller than 40 μm showed higher cumulative migration and decreased XRD retention, while Ni particles larger than 120 μm showed lower migration and post-treatment activity after ammonia leaching. The 40–120 μm particle size range achieved a relatively balanced result in terms of contaminant metal migration, Al retention, molecular sieve structure retention, and micro-reaction activity.
[0098] Verification Example 7; The scale-up group used 1000.0g of dry-based main catalyst, and a quartz tube reactor with an inner diameter of 190mm was used for hydrogen treatment. The bed height was 46-50mm, and the total flow rate of the hydrogen-nitrogen mixed gas was 10.0L / min. The flow rate of the mixed gas per unit dry-based catalyst and the apparent gas velocity of the bed were similar to those in Example 1.
[0099] The leaching process uses a jacketed reactor with a nominal volume of 10L and an inner diameter of 220mm. The working slurry height is about 145mm. The reactor is equipped with four 18mm wide baffles and a four-bladed oblique blade with a diameter of 100mm. The lowest point of the blade is 33mm from the bottom of the reactor. The bottom gas distribution ring has a diameter of 44mm and is evenly distributed with 16 pores with a diameter of 1.1mm.
[0100] The first leachate volume is 5000.0g, the ammonia leaching air flow rate is 5.00L / min, the stirring speed is 225r / min, and the corresponding impeller tip linear velocity is approximately 1.18m / s; The amount of washing water used for each solid obtained from ammonia leaching solid-liquid separation was calculated based on the dry weight of 1000.0g of the main catalyst before hydrogen treatment. 1000.0g of deionized water was added each time. The amount of washing water used after acid leaching, the amount of ammonium nitrate aqueous solution used, and the amount of washing water used after ion exchange were determined proportionally according to the corresponding dry weight basis specified in Example 1. The 10L jacketed reactor is equipped with a reflux condenser that matches its processing capacity. The temperature of the condensate circulating water is 8±2℃. The tail gas is sequentially passed into two absorption bottles, each containing 1000mL of 5% sulfuric acid solution.
[0101] The reactor flushing water and filter flushing water used for transferring the ammonia leaching and acid leaching reaction slurries were also increased proportionally according to the standard scale of unit dry-based catalyst dosage, while the remaining composition, temperature, time, and detection aperture were the same as in Example 1.
[0102] Table 12: Processing results at baseline and scaled-up scales
[0103] Under the condition that the unit dry-based catalyst mixed gas flow rate, air flow rate, bed apparent gas velocity and impeller tip linear velocity are kept similar, the two-stage mobility, Al cumulative mobility, XRD retention and micro-reaction activity of the scale-up group are close to those of the baseline scale.
[0104] Comparative Example 1; Comparative Example 1 simply replaced the hydrogen-nitrogen mixture with 10.0% hydrogen gas fraction used in the hydrogen-containing treatment of Example 1 with 100% nitrogen gas at the same flow rate.
[0105] The phased migration results and the comprehensive processing results are shown in Tables 13 and 14, respectively.
[0106] Comparative Example 2; The main catalyst was subjected to hydrogen treatment and ammonia leaching as in Example 1. After filtration, it was not washed with deionized water three times. The first wet filter cake was directly fed into oxalic acid treatment. Parallel tracing was performed using another batch of the same main catalyst: ammonium bromide was added to the ammonia leaching mother liquor to make the bromide ion mass concentration approximately 500 mg / L, and the actual concentration was measured after stirring for 2 min. A wet filter cake is formed under the same conditions as the main test batch, and bromide ions are extracted and determined using a general tracer method. The tracer is not added to the main test batch.
[0107] It is known that the recovery rate obtained from three parallel recovery tests was 98.7% ± 0.6%, and the mass of mother liquor entrained by the first solid catalyst on a dry basis was 0.328 g / g, corresponding to 31.8 g of mother liquor entrained in the wet filter cake of the main test.
[0108] The mass of metal entering the liquid phase during the ammonia leaching stage is calculated as the sum of the mass of metal in the ammonia leaching filtrate and the mother liquor entrained in the wet filter cake.
[0109] The first wet filter cake was treated with 4.00g of 0.75% oxalic acid aqueous solution per gram of dry basis, without increasing the amount of oxalic acid or adjusting the pH. The mixture was then acid-soaked at 55℃ and 400r / min for 22.5min. The initial pH and the final pH were 8.74 and 8.41, respectively.
[0110] The new migration amount after acid leaching is calculated by subtracting the original metal mass of the mother liquor from the total metal mass in the acid leaching liquid phase. The denominator is the corresponding metal mass that has not yet migrated out of the solid before entering the acid leaching stage. The migration results of each stage are shown in Table 13.
[0111] After the oxalic acid treatment, the subsequent treatment was carried out according to Example 1 to obtain 92.1g of the final catalyst.
[0112] Comparative Example 3; The main catalyst was first subjected to hydrogen treatment and nitrogen cooling as in Example 1. Then, 4.00 g of an oxalic acid aqueous solution with a mass fraction of 0.75% (H2C2O4) was added per gram of dry catalyst. The catalyst was acid-leached at 55°C and 400 r / min for 22.5 min. After filtration and washing with water three times, the resulting solid was treated with a first leaching solution containing 4.00% NH3 and 3.00% effective ammonium carbonate, introduced by ammonia water, at a liquid-to-solid ratio of 5.00:1, at 42.5°C and 500 r / min with continuous air flow at 0.50 L / min for 45 min. No reagents were added to adjust the pH in either leaching unit.
[0113] The phased migration results and the cumulative migration results of A1 are shown in Table 13.
[0114] After the second leaching unit was completed, the subsequent processing was carried out according to Example 1 to obtain 91.4g of the final catalyst.
[0115] Comparative Example 4; This comparative example follows the publicly available acidifying agent combination solution treatment—washing—rare earth exchange route. Hydrochloric acid, ammonium chloride, acetic acid, sodium polyoxyethylene alkylphenol ether sulfonate, and deionized water were weighed to prepare 500.0 g of acidifying agent combination solution, wherein the mass fraction of hydrochloric acid (calculated as HCl) was 1.0%, the mass fraction of ammonium chloride was 7.0%, the mass fraction of acetic acid (calculated as CH3COOH) was 3.0%, the effective mass fraction of sodium polyoxyethylene alkylphenol ether sulfonate was 0.03%, and the remainder was deionized water; The average ethylene oxide addition number of the sodium polyoxyethylene alkylphenol ether sulfonate used is 10, and its dosage is calculated based on the actual measured effective content.
[0116] The main catalyst was added to the acidifying agent mixture and refluxed at 90°C for 3 hours. Then, it was cooled to below 40°C and solid-liquid separation was performed. 5.00 mL of deionized water was added per gram of the initial dry mass of the main catalyst. The resulting filter cake was redispersed, and the pH of the slurry was adjusted to 5.0±0.1 using ammonia. After washing at 60±1°C for 30 minutes, solid-liquid separation was performed.
[0117] The moisture content of the obtained filter cake was determined and its dry weight was calculated. 3.00 mL of RECl3 aqueous solution with a rare earth concentration of 30 g / L (RE2O3) was added per gram of filter cake dry weight, and ion exchange was carried out at 60±1℃ for 1 h. After ion exchange, solid-liquid separation was performed. The resulting filter cake was dried at 120±2℃ for 4 hours, and the drying endpoint was confirmed according to the general constant weight criterion. Then, the temperature was increased to 600℃ in air at 5℃ / min and held for 2 hours. After the temperature in the furnace dropped below 100℃, the catalyst was transferred to a dryer and cooled to room temperature to obtain 90.8g of the final catalyst.
[0118] Following the same liquid phase collection, solid sampling, detection, and calculation methods as in Example 1, the total metal migration rate before rare earth exchange, the cumulative Al migration rate, and the metal mass fraction, XRD retention rate, and microreaction activity of the final product were determined. The results are shown in Table 14.
[0119] Table 13: Staged migration results of Example 1 and Comparative Examples 1-3
[0120] Note: with The data represents the portion that migrated out after oxalic acid treatment, after deducting the original metals from the mother liquor containing ammonia.
[0121] Table 14: Overall Results of Example 1 and Comparative Examples
[0122] Note: The final Ni, V and Fe mass fractions are all determined independently by resampling the final product and are not calculated from the liquid phase migration.
[0123] Example 1 and Comparative Examples 1-4: Pre-ion exchange cumulative Al migration, final XRD retention, and microreactor activity comparison. Figure 2 As shown.
[0124] The results above show that the combination of hydrogen treatment and ammonia-ammonium carbonate leaching under air conditions increases the migration of Ni in the first stage of leaching. The intermediate water washing reduces the neutralization of oxalic acid by alkaline mother liquor, so that the subsequent oxalic acid leaching maintains the migration effect on V and Fe. Sequential connection of each treatment unit can also limit Al migration. Further tests under different process conditions, raw material batches, particle sizes, independent replication, and scale-up experiments demonstrate that the present invention can improve the micro-reaction activity of the reactivated catalyst while maintaining the Y-type molecular sieve structure.
Claims
1. A method for staged acid leaching, demetallization, and reactivation of spent FCC catalysts, characterized in that, include: The spent FCC equilibrium catalyst was classified by particle size using sieves with pore sizes of 120 μm and 40 μm. The particle size that passed through the 120 μm sieve but did not pass through the 40 μm sieve was taken as the main catalyst. The main catalyst was heated to 390–420°C under a nitrogen atmosphere, and treated with a hydrogen-nitrogen mixture with a hydrogen gas fraction of 8%–12% for 20–25 minutes. Then, the gas was switched to nitrogen and cooled to below 100°C. The main catalyst is added to the first leachate, wherein the mass fraction of NH3 introduced by ammonia water in the first leachate is 3.5%–4.5%, and the effective mass fraction of ammonium carbonate (calculated as (NH4)2CO3) is 2.5%–3.5%. The actual dry mass ratio of the first leachate to the main catalyst before hydrogen treatment is 4.5:1–5.5:
1. Under stirring, at 40–45°C, the catalyst is added at a rate of 0.0045–0.0055 L / (g) based on the dry mass. Air is continuously introduced at a flow rate of (min) and ammonia is soaked for 30-60 minutes; After ammonia leaching, solid-liquid separation is performed, and the obtained solid is washed with deionized water until the pH of the final washing solution is 6.5-7.2 at 25±1℃, thus obtaining the first solid catalyst. The first solid catalyst was added to an oxalic acid aqueous solution with an oxalic acid mass fraction of 0.60% to 0.90% (calculated as H2C2O4), wherein the dry mass ratio of the oxalic acid aqueous solution to the first solid catalyst actually entering the acid leaching was 3.5:1 to 4.5:1, and the catalyst was acid-leached at 50 to 60°C for 15 to 30 minutes under stirring. After acid leaching, solid-liquid separation and water washing are performed to obtain a second solid catalyst. The second solid catalyst is then subjected to ammonium nitrate ion exchange, water washing, drying and calcination in sequence to obtain a reactivated FCC catalyst.
2. The staged acid leaching demetallization and reactivation method for spent FCC catalyst as described in claim 1, characterized in that: Before hydrogen treatment, the oxygen volume fraction in the outlet gas was continuously reduced to below 0.5% for 1 minute by replacing it with nitrogen. Nitrogen was then introduced and the temperature was increased to 405℃ at 5℃ / min. After stabilizing at 405±2℃ for 5 minutes, a hydrogen-nitrogen mixture with a hydrogen integral of 10.0% was introduced and treated at 405±2℃ for 22.5 minutes. Subsequently, nitrogen was introduced and the gas was cooled to below 80℃. The flow rates of both nitrogen and hydrogen-nitrogen mixtures are 0.010 L / (g) based on the actual dry mass of the main catalyst added before hydrogen treatment. min).
3. The staged acid leaching demetallization and reactivation method for spent FCC catalyst as described in claim 2, characterized in that: The mass fraction of NH3 introduced by ammonia water in the first leachate is 4.00%, the effective mass fraction of ammonium carbonate calculated as (NH4)2CO3 is 3.00%, and the dry mass ratio of the first leachate to the main catalyst actually added before hydrogen treatment is 5.00:
1. The ammonia leaching temperature was 42.5±1℃, the leaching time was 45 min, and the air flow rate was 0.0050 L / (g) based on the dry basis mass. The stirring speed is 500 r / min.
4. The staged acid leaching demetallization and reactivation method for spent FCC catalyst as described in claim 3, characterized in that: When washing the solid obtained from solid-liquid separation by ammonia leaching, the mass of deionized water added each time is 1.00 times the dry mass of the main catalyst actually added before hydrogen treatment. After washing for 5 minutes at 25±2℃ and 300r / min, solid-liquid separation is performed. A total of three washing processes are carried out.
5. The staged acid leaching demetallization and reactivation method for spent FCC catalyst as described in claim 4, characterized in that: The oxalic acid aqueous solution contains 0.75% oxalic acid by mass (H2C2O4), and the dry mass ratio of the oxalic acid aqueous solution to the first solid catalyst actually entering the acid leaching is 4.00:
1. The acid leaching is carried out at 55±1℃ and 400r / min for 22.5min. After solid-liquid separation by acid leaching, deionized water was added each time at 1.00 times the dry weight of the first solid catalyst entering the acid leaching process. The mixture was then washed for 5 minutes at 25±2℃ and 300r / min before solid-liquid separation was performed. This washing process was repeated three times.
6. The staged acid leaching demetallization and reactivation method for spent FCC catalyst as described in claim 5, characterized in that: The second solid catalyst was subjected to ion exchange using a 6.0% (w / w) ammonium nitrate aqueous solution, wherein the mass of the ammonium nitrate aqueous solution was 5.00 times the dry basis mass of the second solid catalyst actually entering the ion exchange. The ion exchange temperature was 70±1℃, the stirring speed was 400 r / min, and the ion exchange time was 60 min.
7. The staged acid leaching demetallization and reactivation method for spent FCC catalyst as described in claim 5, characterized in that: After ion exchange, the catalyst was each time deionized water was added at 2.00 times the dry weight of the second solid catalyst that actually entered the ion exchange. The catalyst was then washed with slurry at 25±2℃ and 300r / min for 10min, and the washing was repeated three times. The catalyst was then dried at 120±2℃ to constant weight and heated to 500℃ in air at 5℃ / min and held at that temperature for 2h.
